STATE AND PROSPECTS OF UKRAINIAN-US COOPERATION IN THE CONDITIONS OF ARMED AGGRESSION BY RUSSIA AGAINST UKRAINE - Zelinska, O. M.; Galaziuk, N. M. (The actual problems of regional economy development, 2024)
The relevance of the study of economic and diplomatic communication between Ukraine and the USA is determined by the modern dynamic world political situation, full of conflicts and economic instability. The dialogue between the two countries acquires new realities that call into question the traditional norms and strategies of exchange. In the conditions of geopolitical upheavals, such as growing Russian aggression, the Ukrainian crisis and the changing situation in the world, the importance of economic and diplomatic cooperation acquires strategic importance. If Ukraine can effectively defend its position, protect its own interests and mobilize the support of the international community, this will directly affect its security, stability and future. Russia's full-scale military aggression against Ukraine led to the destruction and damage of civilian and critical infrastructure, which caused external and internal migration of the working population. Under such circumstances, the national economy faced an economic crisis. After a period of adaptation, world trade has built new logistics chains, but global food security remains in a precarious position. However, wars tend to end, so participation in international cooperation, including with the USA, is of great importance for the recovery of the national economy. The problem of post-war reconstruction of the country after the war is not a new practice in world history. The manner in which cooperation takes place, in particular in the context of reconstruction, is largely influenced by the peculiarities of individual states. Therefore, the use of specific economic instruments can have both positive and negative effects. The study of this issue will provide an opportunity to better understand how international cooperation affects economic recovery and will help the state to return to the international trade arena as soon as possible. Ukrainian-American cooperation always attracts the attention of both scientists and practitioners. First of all, due to its strategic nature, this cooperation requires greater responsibility and meaningfulness of the actions of both states. Also, an effective diplomatic and economic dialogue with the USA has a direct impact on the formation of Ukraine as an active member of the world community. The purpose of the work is to research the economic and diplomatic cooperation between Ukraine and the United States of America, and to identify on this basis the prospects for further cooperation in the process of post-war reconstruction of our state in the context of the Russian invasion. To achieve the goal of the scientific work, the following general scientific research methods are applied: logical, comparison, synthesis and analysis, generalization, classification, explanation, as well as statistical, tabular and graphic methods. The practical significance of the results obtained in the research process is that its conclusions and recommendations can be used for further scientific research on this topic and will help to analyze aspects that will directly affect the recovery of the Ukrainian economy in the process of developing Ukrainian-American cooperation in post-war conditions with the help of modeling the effectiveness of the formed decisions involving the resource potential of Ukraine.